Turbulence and Particle Acceleration in Shearing Flows - Rieger, Frank M.; Duffy, Peter (The astrophysical journal. Part 2, Letters, 2021)
We explore constraints imposed by shear-driven instabilities on the acceleration of energetic particles in relativistic shearing flows. We show that shearing layers in large-scale AGN jets are likely to encompass a sizeable fraction (≳0.1) of the jet radius, requiring seed injection of GeV electrons for efficient acceleration. While the diffusion process may depend on predeveloped turbulence if injection occurs at higher energies, electron acceleration to PeV and proton acceleration to EeV energies appears possible within the constraints imposed by jet stability.